Studi Kasus Putusan Pengadilan Tinggi Mataram Nomor 183/PDT/2023/PT MTR tentang Pemeriksaan Setempat Gugatan Kurang Pihak dan Implikasi Putusan terhadap Objek Sengketa - Soraya Firmansjah; Artaji Artaji; Rai Mantili (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Mataram High Court Decision Number 183/PDT/2023/PT MTR, which upheld the Selong District Court Decision Number 59/PDT/2023/PN SEL, stated that the Appellants' (formerly the Plaintiffs) lawsuit was inadmissible because there were parties who had not been involved in the case (lack of parties). The legal fact regarding this lack of parties had actually emerged since the on-site examination stage conducted by the Panel of Judges at the first instance. In fact, this had also been expressly conveyed by the Appellees (formerly the Defendants) through an exception. However, the Panel of Judges rejected the exception and ultimately contradictorily declared the lawsuit inadmissible. This study emphasizes the urgency of considering the results of the on-site examination in relation to the lack of parties and its implications for the ownership status of the disputed object after the decision. The research method used is a normative juridical approach, with analysis referring to statutory provisions, legal doctrine, and civil law principles. Specifically, this study highlights the law of evidence and the position of on-site examination in the judicial process. The research results show that on-site inspections actually play a crucial role in assessing evidence and witness statements related to the existence of parties who should be called into the lawsuit. However, this urgency is lost because the panel of judges' considerations are inconsistent with the provisions regarding the strength of evidence as stipulated in Article 284 of the RBg. Furthermore, the exception regarding the lack of parties whose substance is similar to the results of the on-site inspection is actually set aside. A further implication of this decision is that the ownership status of the disputed object does not change. After the decision is rendered, the object remains in the possession of the Respondents, without legal clarity regarding who the party legally has authority over it.